Badanie frakcjonowania wybranych metali ciężkich w osadach dennych środkowej Odry = Ingrediens of fractionetion heavy metals in bottom sediments of middlie Odra river - Głosińska, Grażyna; Sobczyński, Tadeusz; Siepak, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Fractionation of Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn has been performed in bottom sediment samples collected along a 75 km section of the middle Odra River by a modified method of 5-step sequential extraction according to Tessier. The results have shown the presence of Cu, Ni, Zn and Mn already in exchange fraction (I).
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); metale ciężkie; osady denne; frakcjonowanie; biodostępność; Odra; heavy metals; bottom sediments; fractionation; bioavailability